Fallacy of the criminal law doctrine of "last seen": a look at legal causation in homicide cases in Nigeria - Alili, Ngozi (African journal of law and criminology, 2015)
Causation as a criminal law concept is the link or bridge between forbidden conducts and the resultant effect of bringing them about by human agents called accused persons. Two types of causation govern the criminal law. These are factual and legal causation. This paper took a deep look at legal causation which finds expression in interferences, presumptions and circumstantial evidence all of which merge into the “last seen” doctrine mainly applicable in culpable homicide cases with particular reference to Nigeria, where the appellate courts seem to have elevated the doctrine to substantive law though without enabling legislation and without recourse to the negative effect of its rigid application on the fundamental rights of accused persons and on our adversary system of criminal justice adjudication. The doctrine calls on the person last seen with the deceased in homicide cases to explain how the deceased met his or her death in the absence of which explanation, such a person is said to be the murderer. It was observed that a rigid application of the doctrine imposes on the accused a “reverse burden” of proof by calling upon him to prove his innocence. The doctrine violates our adversary criminal justice system as practised in all common law jurisdictions and the accused’s constitutional right to silence in the face of criminal allegations as well as his presumption of innocence until proven guilty by a court of competent jurisdiction. It was concluded that much as presumptions, inferences and circumstantial evidence aid judicial proceedings in most common law jurisdictions the last seen doctrine which is an integral part of circumstantial evidence should be sparingly applied with much caution in homicide cases given the consequences of possible convictions for such cases so as to guard against a miscarriage of justice. A legislative intervention to curtail judicial excesses of the Nigerian appellate courts in this area of the law was called for.